Implementation of an evidence-based model of care for low back pain in emergency departments: protocol for the Sydney Health Partners Emergency Department (SHaPED) trial. Issue 4 (19th April 2018) - Machado, Gustavo C; Richards, Bethan; Needs, Chris; Buchbinder, Rachelle; Harris, Ian A; Howard, Kirsten; McCaffery, Kirsten; Billot, Laurent; Edwards, James; Rogan, Eileen; Facer, Rochelle; Lord Cowell, David; et al.
Abstract : Introduction: Patients with low back pain often seek care in emergency departments, but the problem is that many patients receive unnecessary or ineffective interventions and at the same time miss out on the basics of care, such as advice on self-management. This pattern of care has important consequences for the healthcare system (expensive and inefficient) and for patients (poor health outcomes). We hypothesised that the implementation of an evidence-based model of care for low back pain will improve emergency care by reducing inappropriate overuse of tests and treatments and improving patient outcomes. Methods and analysis: A stepped-wedge cluster randomised controlled trial will be conducted to implement and evaluate the use of the Agency for Clinical Innovation (ACI) model of care for acute low back pain at four emergency departments in New South Wales, Australia. Clinician participants will be emergency physicians, nurses and physiotherapists. Codes from the Systematised Nomenclature of Medicine—Clinical Terms—Australian version will be used to identify low back pain presentations. The intervention, targeting emergency clinicians, will comprise educational materials and seminars and an audit and feedback approach. Health service delivery outcomes are routinely collected measures of imaging (primary outcome), opioid use and inpatient admission. A random subsample of 200 patient participants from each trial period will be included to measure patient outcomes (pain intensity, physical function, quality of life and experience with emergency service). The effectiveness of the intervention will be assessed by comparing the postintervention period with the retrospective baseline control period. Ethics and dissemination: The study received ethical approval from the Sydney Local Health District (Royal Prince Alfred Hospital zone) Ethics Committee (X17-0043). The results of this study will be published in peer-reviewed journals and presented at international conferences. Trial registration number: Australia New Zealand Clinical Trials Registry: ACTRN 12617001160325.